O desenvolvimento do portador de necessidades especiais de 5 a 7 anos através da metodologia ativa: um estudo de caso em Rio Pardo - Berger, Sâmara Bittencourt (2004)
This work consists of a study that has as objective investigate how active classes helping on the development of infants with special bearers of needs with mental defi-ciency, encouraging the use from the creativity, challenging the initiative, emphasiz-ing the resolution of problems, applying a program of activities, games, jokes and toys in physical education assets sessions, encouraging creative, intellectual, and corporal abilities of development. The subjects of this study were 6 infants from 5 to 7 years old, boys that study at Special School Renascer - APAE at Rio Pardo /RS, since the two first years of their life in stimulation classes. The infants participated actively of 35 physical sessions of education applied, where they were analyzed qualitative and quantitative aspects of their development. In this it researches quali-tative, that is characterized like a study of case ethnographic, the facts were collected through the observation participant, analysis of documents, filming, pictures and newspaper of field. It verified that this active methodology is utilized since the stimu-lation groups from the childlike education, in physical sessions of education, contrib-uting of significant form in the development of the special bearers of needs, specificly in the corresponding aspects to motricity global, expression sensorial, time space organization, memorization, reasoning, imagination, oral expression, cooperation, creativity and autonomy.